2013
DOI: 10.3368/le.89.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Risk Preferences, Risk Perceptions, and Flood Insurance

Abstract: We combine household-level data on the choice to purchase flood insurance with experiment-based risk preference data and subjective risk perception data. The sample covers a wide geographic area (the entire U.S. Gulf Coast and Florida's Atlantic Coast) and includes individuals exposed to varying levels of risk. This work represents one of very few analyses to do so. Results indicate that our experiment-based measure of risk aversion over the loss domain positively and significantly correlates with the decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
126
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 68 publications
16
126
1
Order By: Relevance
“…In other words, a risk-averse farmer would be more willing to buy the agricultural weather index insurance. This is consistent with standard economic theory and the existing literature on the linkage between individuals' risk preferences and insurance uptake decisions (Petrolia et al 2013;Simon and Fiorentino 2014). Thus, it can be anticipated that more risk-averse individuals, such as female farmers, would be more likely to take up the weather index-based insurance.…”
Section: 65supporting
confidence: 75%
See 2 more Smart Citations
“…In other words, a risk-averse farmer would be more willing to buy the agricultural weather index insurance. This is consistent with standard economic theory and the existing literature on the linkage between individuals' risk preferences and insurance uptake decisions (Petrolia et al 2013;Simon and Fiorentino 2014). Thus, it can be anticipated that more risk-averse individuals, such as female farmers, would be more likely to take up the weather index-based insurance.…”
Section: 65supporting
confidence: 75%
“…This finding is expected and understandable. If individuals consider that the probability or potential magnitude of loss is low, insurance may appear unattractive, even at subsidized rates (Petrolia et al 2013). The literature also shows that individuals often underestimate the risk (Camerer and Kunreuther 1989;Chivers and Flores 2002;Kunreuther 2006).…”
Section: 65mentioning
confidence: 99%
See 1 more Smart Citation
“…The CRS program resembles conventional environmental policy as a top-down directive or subsidy, but it departs from typical US federal environmental policy in that it bypasses state governments, directly targets local governments, and ostensibly promotes provision of local commons-community flood resilience. Even as major programs like the NFIP emphasize insurance for private property owners (FEMA 2011), Landry and Jahan-Parvar (2011), Petrolia et al (2013), and Poussin et al (2014) focus on flood mitigation activities of individual households, but did not examine how CRS incentives affect what participating communities do. Much less is known about flood mitigation activities by communities.…”
Section: Factors Influencing Crs Participationmentioning
confidence: 99%
“…Social marketing could be used to bring about behavioral change in the perceptions of people towards adopting disaster insurance as a form of financial literacy. Petrolia, Landry, and Coble (2013) in their study of the impact of subjective risk perception and preference on the enrolment in flood insurance program is positively correlated with the risk aversion, the perceived expected loss, eligibility for disaster assistance, and credibility of insurance providers. They found that mitigation efforts through Community Rating Systems (CRS) 1 generally improved the insurance penetration levels.…”
Section: Tackling the Issue Of Underinsurancementioning
confidence: 99%